Mary Mother of Hope in the Writings of Blessed Honorat Koźmiński - Synowczyk OFMCap, Kazimierz (Studia Teologiczne Białystok Drohiczyn Łomża, 2025)
This article discusses Mary, Mother of Hope, in the writings of Blessed Honorat Koźmiński. Father Honorat's reflection begins with the maternal mediation of the Blessed Virgin Mary in the lives of the faithful and her help in our process of identification with Christ. Father Honorat speaks of Mary, Mother of Hope, from a threefold perspective: in the life of the Church, in the history of the Polish nation, and in the personal experience of trust placed in the Virgin Mary, Mother of Hope. The main sources for the analysis of this subject are the following writings of Father Honorat Koźmiński: the Spiritual Diary, the Story of Stories, and the meditations of May, those of the rosary, and those dedicated to the apparitions of the Madonna at Gietrzwałd. The analysis of the Beatitude's statements confirms a vision of Mary as the dispenser of hope and a model of this theological virtue for all the faithful.